PERANCANGAN APLIKASI PENJUALAN BERBASIS WEB PADA TB 3 UTAMA - Felix Tandano; Ery Dewayanti (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The design of a web-based sales application for TB 3 Utama aims to enhance efficiency and market reach through a digital platform. With the rapid development of technology, the need for a sales information system that can be accessed online is becoming increasingly important. This website is equipped with features such as account registration, product search, shopping cart, order history, and an admin dashboard to manage products and sales reports. The Waterfall methodology is applied in the development of this system, through the stages of requirement analysis, design, implementation, testing, and maintenance. The testing results show that the application meets the needs of TB 3 Utama, provides a more organized shopping experience for customers, and improves operational efficiency. Development suggestions include the addition of automatic notifications and optimization of the responsive display for mobile devices to further support user experience.